2023
DOI: 10.3389/fmicb.2023.1166148
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of rhizospheric phageome of the wild plant species Moringa oleifera

Abstract: IntroductionThe study aims to describe phageome of soil rhizosphere of M.oleifera in terms of the genes encoding CAZymes and other KEGG enzymes.MethodsGenes of the rhizospheric virome of the wild plant species Moringa oleifera were investigated for their ability to encode useful CAZymes and other KEGG (Kyoto Encyclopedia of Genes and Genomes) enzymes and to resist antibiotic resistance genes (ARGs) in the soil.ResultsAbundance of these genes was higher in the rhizospheric microbiome than in the bulk soil. Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 122 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…This finding revealed that Pseudomonas tend to host more functional genes than Hydrogenphaga . Correspondent to our discovery, Ashy et al also concluded that Pseudomonas was a key host for viral genes and antibiotic resistance genes in the rhizosphere of moringa ( Moringa oleifera ) ( Ashy et al, 2023 ). In the soil sample of spinach treated with water, Stenotrophomonas and Agrobacterium were not abundant genera, but hosted relatively large amounts of functional genes.…”
Section: Resultsmentioning
confidence: 58%
“…This finding revealed that Pseudomonas tend to host more functional genes than Hydrogenphaga . Correspondent to our discovery, Ashy et al also concluded that Pseudomonas was a key host for viral genes and antibiotic resistance genes in the rhizosphere of moringa ( Moringa oleifera ) ( Ashy et al, 2023 ). In the soil sample of spinach treated with water, Stenotrophomonas and Agrobacterium were not abundant genera, but hosted relatively large amounts of functional genes.…”
Section: Resultsmentioning
confidence: 58%
“…From the stem of M. oleifera, compounds such as vanillin, β-sitosterol, β-sitostenone, 4-hydroxymellin, and octacosanoic acid have been identified. It has been discovered that Moringa oleifera contains L-arabinose, galactose, glucuronic acid, L-rhamnose, mannose, and xylose (Ashy et al, 2023).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Bacteria and phages are the most abundant host-parasite system on Earth (36,37). Phages play key roles in animal microbiomes and plant rhizospheres by maintaining microbiome diversity and providing protection from invasive pathogens (38)(39)(40)(41). They are also increasingly viewed as potential therapeutic alternatives to antibiotics given growing levels of antimicrobial resistance (42)(43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%